The Impact of the Indonesian Zakat Initiative (IZI) Program on IncreasingIncome and Welfare of MSMEs in South Sumatra - Citra Pertiwi; Citra Lestari (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2026)
The MSME empowerment program initiated by the Indonesian Zakat Initiative (IZI) of South Sumatra analyzes the impact of increasing micro-enterprise income and its impact on beneficiary mustahik (the beneficiaries). This program provides business capital assistance and carts as an empowerment effort for mustahik who own micro-enterprises. Using qualitative descriptive research methods, data was collected through observation, interviews, and documentation with informants from the beneficiary community. The results showed that before receiving assistance, micro-enterprises faced significant obstacles related to limited capital, including unsuitable carts. After participating in the IZI South Sumatra MSME program, beneficiaries were able to run their businesses better, overcome capital shortages, and directly impacted income increases.